Sintesis C-dots dari Gula Pasir dan Asam Sitrat untuk Deteksi Logam Berat - Dona, Rahma; Ikhtiarudin, Ihsan; Yanto, Yanto (LPPM Universitas Muhammadiyah Riau, 2023)
Heavy metal contamination is one of the problems in pharmaceutical products. Carbon dots are a practical and economical method of heavy metal detection to reduce heavy metal contamination in pharmaceutical products. Carbon dots have been successfully synthesized by microwave irradiation from sugar table doped with urea fertilizer (CD-GU) and citric acid doped with urea fertilizer (CD-AU). The success of the synthesis of carbon dots can be seen from their properties that produce a blue to green luminescence when excited with a 405 nm laser and an orange to red luminescence when excited with a 532 nm laser. When excited with a 405 nm laser, CD-GU produces a strong light blue luminescence, while CD-AU produces a strong green luminescence. CD-GU and CD-AU also exhibit orange luminescence when excited with a 532 nm laser. The intensity of luminescence of carbon dots will decrease when interacting with heavy metals so that it can be applied for heavy metal detection. The results of this study revealed that CD-GU and CD-AU can be used to detect heavy metals.